THE RIGHT TO PRIVACY UNDER ARTICLE 8 OF THE EUROPEAN CONVENTION OF HUMAN RIGHTS AND LEGALITY OF EPIDEMIOLOGICAL MONITORING MEASURES TO COMBAT THE COVID-19 VIRUS PANDEMIC - Jelena S. Milenković (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
In the paper the author analyzes the issue of the protection of the right to privacy according to Article 8 of the European Convention on Human Rights at the time of the pandemic of the virus Covid 19. At the beginning of the pandemic, European countries faced a large number of infected people and the collapse of health systems in some countries. The question that arises is whether such a situation that escaped control was caused by the non-implementation of measures of epidemiological monitoring of citizens to the extent and manner in which these measures were implemented in the Far East, respectively whether the democratic system remained unprotected precisely because of respect for democratic human rights standards, specifically the right to privacy. Given that epidemiological monitoring measures are currently the most important way to combat the Covid 19 virus pandemic, it is necessary to consider fulfilling the condition of legality of these measures of interference by European countries in the privacy of citizens. The answer to the question of the definition of the concept of the right to privacy, as well as whether epidemiological monitoring measures fall into this corpus, we came to a detailed analysis of the case law of the European Court of Human Rights, which protects the rights guaranteed by the European Convention on Human Rights, inter alia, the right to private life. By analyzing the case law of the European Court of Human Rights, we have come to the conditions that must be met in order for epidemiological monitoring measures to be considered legal.